MAKING 3D ARCHITECTURAL ANIMATIONS TO INTRODUCE THE KOTAKU WORK PROGRAM IN BATAM FROM THE MEMBER OF DPR RI CEN SUI LAN - Jimmy Pratama; Indo Dicaprio Pratama (ConCEPt - Conference on Community Engagement Project, 2022)
Representatives from members of DPR RI Cen Sui Lan who is located at the Orchid Business Center are important to assist Ms. Cen Sui Lan in introducing her work projects, one of which is KOTAKU. KOTAKU program has several outcomes to be achieved and one of them is the construction of an Open Public Area (OPA) in Batam. The lack of 3D animation as a medium is the main problem in the introduction of the output because it is still in the form of a 3D model. The method that will be used is applied research starting from problem identification, content design, content development, content testing to content evaluation. The results of this study are in the form of a video file that briefly describes the KOTAKU project using motion graphics and the OPA architectural 3D animation that will be sent using the (.mp4) format. With the development of this video, the recipient can use the video as a medium for delivering information which is expected to introduce the KOTAKU project, especially in the construction of the OPA in Batam.